Freedom and justice in human behavior: socio-historical essay - Rubanau, Anatoly V. (Journal of the Belarusian State University. Sociology, 2019)
Meaning and understanding of freedom and justice in human behavior and social movements are explicated. Evolution of content of concepts of freedom and justice in various periods and their role in orientation of masses in revolutions in France in the 18th century and in Russia in the 20th century are analyzed. Main zones of intensive feelings about the phenomena of freedom and justice in contemporary society are stated. Author argues that freedom is understood as closely related to realization of human rights, expression of personal freedom and group identity. Main violations of social justice are presented as results of contradictions between rich North and poor South.
Keywords: freedom; justice; social behavior; social movements; historical sociology